Process performance evaluation and improvement for the quality progress in the industrial manufacturing systems - (:unkn) unknown (My University, 2006)
As the competition gets tougher, there is more pressure on manufacturing sectors to improve quality and customer satisfaction while decreasing cost and increasing productivity. These can be achieved by using modern quality management systems and process improvement techniques to reduce the process variability and driven waste within manufacturing process using effective application of statistical tools. There are a number of different methods for collecting and evaluation data. One of them is pre-control. Pre-control is a technique that helps shop operators to control the process so that defective parts are not produced. This technique is also simple to understand for the shop operators and statistically robust. In this study, it was used this techniques for the quality progress of the production parts with one-sided geometrical tolerances. Copyright© (2006) by the International Measurement Federation (IMEKO).
Keywords: Process improvement; quality progress; reduction of process variability